Synergism between plant extract and antimicrobial drugs used on Staphylococcus aureus diseases - Betoni, Joyce Elaine Cristina [UNESP]; Mantovani, Rebeca Passarelli [UNESP]; Barbosa, Lidiane Nunes [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Fernandes Junior, Ary [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2006)
Searches for substances with antimicrobial activity are frequent, and medicinal plants have been considered interesting by some researchers since they are frequently used in popular medicine as remedies for many infectious diseases. The aim of this study was to verify the synergism between 13 antimicrobial drugs and 8 plant extracts - guaco (Mikania glomerata), guava (Psidium guajava), clove (Syzygium aromaticum), garlic (Allium sativum), lemongrass (Cymbopogon citratus), ginger (Zingiber officinale), carqueja (Baccharis trimera), and mint (Mentha piperita) - against Staphylococcus aureus strains, and for this purpose, the disk method was the antimicrobial susceptibility test performed. Petri dishes were prepared with or without dilution of plant extracts at sub-inhibitory concentrations in Mueller-Hinton Agar (MHA), and the inhibitory zones were recorded in millimeters. In vitro anti-Staphylococcus aureus activities of the extracts were confirmed, and synergism was verified for all the extracts; clove, guava, and lemongrass presented the highest synergism rate with antimicrobial drugs, while ginger and garlic showed limited synergistic capacity.
Keywords: medicinal plants; Staphylococcus aureus; antimicrobial drugs; synergism; Kirby & Bauer method